2014
DOI: 10.3103/s0884591314030040
|View full text |Cite
|
Sign up to set email alerts
|

Charged particle acceleration in the front of the shock wave bounding supersonic solar wind

Abstract: The process of cosmic ray acceleration in the front of the spherical shock wave bounding the supersonic solar wind is studied. On the basis of our analytical solution of the transport equation, the energy and spatial distributions of cosmic ray intensity and anisotropy are investigated. It is shown that the shape of accelerated particle spectrum is determined by the medium compressibility at the shock front and by cosmic ray modulation parameters. Fig. 6. Spatial distribution of cosmic rays. J + is the flux of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…In fact, Lindzen 10 found that the breaking of gravity wave can produce wave damping in the middle atmosphere; furthermore, Holton and Wehrbein 11 pointed that the breaking of gravity wave can supply most frictional dissipation for stratosphere and middle atmosphere and describe the dissipation process using Rayleigh friction parameterization; Hirst 12 also employed Rayleigh friction to research large-scale pattern. The research of Fedorov 13 indicated that the dynamics behavior of upper atmosphere is decided by nonlinear and molecule viscous loss, the Rayleigh friction increases with the rising of altitude and the viscous friction increases with the rising of temperature in middle atmosphere. Except the bottom of stratosphere, the order of magnitudes of Rayleigh friction coefficient and viscous friction coefficient are both 10 À6 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Lindzen 10 found that the breaking of gravity wave can produce wave damping in the middle atmosphere; furthermore, Holton and Wehrbein 11 pointed that the breaking of gravity wave can supply most frictional dissipation for stratosphere and middle atmosphere and describe the dissipation process using Rayleigh friction parameterization; Hirst 12 also employed Rayleigh friction to research large-scale pattern. The research of Fedorov 13 indicated that the dynamics behavior of upper atmosphere is decided by nonlinear and molecule viscous loss, the Rayleigh friction increases with the rising of altitude and the viscous friction increases with the rising of temperature in middle atmosphere. Except the bottom of stratosphere, the order of magnitudes of Rayleigh friction coefficient and viscous friction coefficient are both 10 À6 s À1 .…”
Section: Introductionmentioning
confidence: 99%